AGROFORESTRY TO IMPROVE SOIL HEALTH: MICROBIAL BIOMASS NITROGEN (MBN) AS AN INDICATOR - Pradani, Avi Qurvanda Putri; Nurfadilah; Sari, Rika Ratna; Danny Dwi Saputra; Hairiah, Kurniatun (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Conversion of forests into agricultural land is one of the environmental problems currently being faced, leading to various environmental challenges including the decline in soil health. One effort to improve land management and slow down land degradation is to plant various types of trees and intercrops through an agroforestry system. Agroforestry is considered a viable strategy to gradually create a conducive microclimate for soil biota that can improve the physical, chemical and biological properties of the soil. The biomass of microorganisms as quantified – Microbial Biomass Nitrogen (MBN) and Microbial Biomass Carbon (MBC) – has been proposed as sensitive indicator of soil change. This research aimed to understand how MBN responds to agroforestation of Imperata grasslands in Solok Regency, West Sumatra (Indonesia). Fields of eight land use types (in three replications each) were sampled in the Juli-August 2024 period. Plot characteristics such as canopy cover were measured, to compare with MBN and MBC for soil at a depth of 0-10 cm. The results showed statistically significant differences in MBN and MBC in various land uses,  that match differences in canopy cover and age of agroforestry systems. A 1% increase in canopy cover could increase soil MBN levels with 0.94 mg kg-1 (R2 = 0.90). The C:N ratio for microbial biomass varied in the 2-6 range, with the lowest values for intensively cropped land, and the highest for existing or recently converted Imperata grasslands.